2019
DOI: 10.1111/mec.14929
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying long‐term recurrence in planktonic microbial eukaryotes

Abstract: How much temporal recurrence is present in microbial assemblages is still an unanswered ecological question. Even though marked seasonal changes have been reported for whole microbial communities, less is known on the dynamics and seasonality of individual taxa. Here, we aim at understanding microbial recurrence at three different levels: community, taxonomic group and operational taxonomic units (OTUs). For that, we focused on a model microbial eukaryotic community populating a long‐term marine microbial obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

19
123
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 88 publications
(142 citation statements)
references
References 67 publications
19
123
0
Order By: Relevance
“…have developed a new Recurrence Index (RI) to specifically address this question on a rich data set of plankton samples collected monthly over 10 years at the Blanes Bay Microbial Observatory (Mediterranean Sea) and submitted to 18S rRNA gene metabarcoding analysis. For both eukaryotes and prokaryotes, a recurrent observation in previous marine plankton metabarcoding analyses is that diversity is most often dominated by rare OTUs occurring at very low frequencies and in single or very few samples(Pedrós-Alió, 2006) Giner et al (2019). corroborated this expectation and, by applying their RI index, they found that only 13% and 19% of the pico-and nano-eukaryotic OTUs, respectively, showed seasonality.…”
mentioning
confidence: 56%
See 4 more Smart Citations
“…have developed a new Recurrence Index (RI) to specifically address this question on a rich data set of plankton samples collected monthly over 10 years at the Blanes Bay Microbial Observatory (Mediterranean Sea) and submitted to 18S rRNA gene metabarcoding analysis. For both eukaryotes and prokaryotes, a recurrent observation in previous marine plankton metabarcoding analyses is that diversity is most often dominated by rare OTUs occurring at very low frequencies and in single or very few samples(Pedrós-Alió, 2006) Giner et al (2019). corroborated this expectation and, by applying their RI index, they found that only 13% and 19% of the pico-and nano-eukaryotic OTUs, respectively, showed seasonality.…”
mentioning
confidence: 56%
“…For both eukaryotes and prokaryotes, a recurrent observation in previous marine plankton metabarcoding analyses is that diversity is most often dominated by rare OTUs occurring at very low frequencies and in single or very few samples (Pedrós‐Alió, ). Giner et al () corroborated this expectation and, by applying their RI index, they found that only 13% and 19% of the pico‐ and nano‐eukaryotic OTUs, respectively, showed seasonality. However, these OTUs represented a large proportion of the sequence reads (39% and 37%, respectively), indicating that they are quantitatively important members of the small‐size eukaryotic plankton community.…”
mentioning
confidence: 82%
See 3 more Smart Citations